2017
DOI: 10.1002/jbmr.3094
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphate Is Associated With Fracture Risk: The Rotterdam Study and MrOS

Abstract: Extreme phosphate levels (P) have been associated with mineralization defects and increased fracture risk. Whether P within normal range is related to bone health in the general population is not well understood. To investigate the association of P with bone mineral density (BMD) and fracture risk, we assessed two population-based cohorts: the Dutch Rotterdam Study (RS-I, RS-II, RS-III; n=6791) and the US Osteoporotic Fractures in Men (MrOS; n=5425) study. The relationship of P with lumbar spine (LS) and femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 67 publications
5
37
0
Order By: Relevance
“…In population-based cohorts, serum phosphate levels are positively associated with fracture risk in both sexes and in a subgroup of men with CKD. 107 This was maintained after adjustment for FGF23 and PTH, which indicates that high phosphate itself and not underlying hormonal disturbances may explain the high fracture risk. Reduced bone mass and increased fracture risk associated with hyperphosphatemia could be mediated by a lower osteoblastic proliferation through insulin growth factor 1 and osteopontin gene expression.…”
Section: -75mentioning
confidence: 85%
“…In population-based cohorts, serum phosphate levels are positively associated with fracture risk in both sexes and in a subgroup of men with CKD. 107 This was maintained after adjustment for FGF23 and PTH, which indicates that high phosphate itself and not underlying hormonal disturbances may explain the high fracture risk. Reduced bone mass and increased fracture risk associated with hyperphosphatemia could be mediated by a lower osteoblastic proliferation through insulin growth factor 1 and osteopontin gene expression.…”
Section: -75mentioning
confidence: 85%
“…Additionally, accurate assessment of dietary phosphorus intake from food frequency questionnaires is limited by participant errors as well as incomplete and inaccurate nutrient database content (15). Campos-Obando et al (53) also note that the increased fracture risk associated with serum phosphate was observed within the normal range for serum phosphate, which may suggest that usual intakes are too high. However, whether dietary phosphorus intake affects serum phosphate levels within the normal range remains unclear.…”
Section: High Dietary Phosphorus Intake Effects On Bone Healthmentioning
confidence: 98%
“…In contrast, in a Brazilian cohort with low average calcium intake (~400 mg/d), for each increase of 100 mg/d in dietary phosphorus there was a 9% increase in fracture risk (52). Recently, a combined analysis of the relationship between serum phosphate and fracture risk in the Rotterdam Study and MrOS prospective cohorts was reported by Campos-Obando et al (53). Serum phosphate was positively related to fracture risk, where there was a 47% increased risk of fracture with each 1 mg/dL increase in serum phosphate after adjusting for multiple covariates.…”
Section: High Dietary Phosphorus Intake Effects On Bone Healthmentioning
confidence: 99%
“…A previous study showed that older men and women, even without overt kidney disease, have an increased fracture risk with increasing serum phosphate concentrations, even when these are within the normal range, and independently of bone mineral density. 92 Whether this increased fracture risk is directly related to serum phosphate concentration or to underlying changes in phosphate-regulating hormones, such as osteocyte-derived FGF23, α-Klotho, parathyroid hormone, or 1,25-hydroxyvitamin D, remains unknown. FGF23 is a hormone secreted by osteocytes in the bone, which together with its co-factor α-Klotho inhibits phosphate reabsorption and 1,25-hydroxyvitamin D production in the kidney.…”
Section: Calcium and Bone Homoeostasismentioning
confidence: 99%